Neighborhood Connected Two -Outdegree Equitable Domination of the ϑ-Obrazom Graphs of P_n,G_n and H_n - Ameenal Bibi, K.; Rajakumari, P. (International Journal of Engineering and Technology, 2018)
Let G=(V,E) be a connected graph. A two-outdegree equitable dominating set D of a graph G is called the neighborhood connected two-outdegree equitable dominating set (nc2oe-set) if the induced sub graph <N(D)> is connected. The minimum cardinality of the minimal neighborhood connected two-outdegree equitable dominating set is called neighborhood connected two-outdegree equitable domination number of G and is denoted by . In this paper, we initiated the a study of this parameter and obtained for the -obrazom graphs of and . Also, we investigated the two-outdegree equitable domination number of the -obrazom graphs of and .